Internet and democracy – perspectives of development - A. V. Bykov (Сибирское юридическое обозрение, 2013)
The article is devoted to one of the most perspective ways of democratic principles improvement. Some issues and problems of social-state relations based on the use of modern information technology are considered. The material has been prepared on the basis of the open Internet sources analysis.